EXPERIENCE OF DOING ENDOSCOPIC SINUS SURGERY FOR CHRONIC MAXILLARY SINUSITIS WITHOUT PRE-OPERATIVE CT-SCAN IN A PERIPHERAL HOSPITAL - Asghar, Adnan; Aslam, Sohail; Bukhari, Syed Muhammad Asad Shabbir; Ijaz, Umar; Iqbal, Shahid; Latif, Saira (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine frequency of our complications of endoscopic sinus surgery without pre-operative CT-Scan and to compare this frequency with other similar studies done with the help of pre-operative CT-Scans. Study Design: Cross sectional study. Place and Duration of Study: ENT Department, Combined Military Hospital Skardu Pakistan, from Jun 2017 to Jun 2019. Methodology: Total 69 patients (116 Sides) were operated under general anesthesia by using 0 and 30 degree endoscopes to address the Maxillary sinusitis. Frequency of complications was compared to other studies by applying chi-square test for goodness of fit. The complications were also correlated to ages of patients by applying Spearman correlation analysis. Results: Mean age was 29.75 ± 10.9 years (range 15-75). Overall complications rate was 4.3% (5 out of 116 sides, 95% confidence interval 4.23-4.4). Peri-orbital ecchymosis and peri-orbital emphysema were most commonly occurring complications (4.3%). This complication rate was compared to few other studies, which proved that difference was not statistically significant. Correlation of occurrences of orbital complications with the age proved that there was no statistically significant correlation (Correlation coefficient r=-0.085, p-value 0.276). Conclusion: Isolated chronic maxillary sinusitis refractory to medical treatment can be treated by endoscopic sinus surgery without pre-operative CT-Scan.